2006
DOI: 10.1016/j.ejcts.2005.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Total arch replacement using a stepwise distal anastomosis for arch aneurysms with distal extension☆

Abstract: A total of 120 patients having arch to distal arch aneurysm with downstream extension underwent total arch replacement, with individual arch-vessel reconstruction through median sternotomy using a novel "stepwise" distal aortic anastomosis. Cardiopulmonary bypass was established by cannulating the right axillary artery and the ascending aorta or femoral artery. Hypothermia was at 22-28 degrees C. Through the aneurysm, the descending aorta was divided. Distal anastomosis using the stepwise technique was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 8 publications
0
39
0
Order By: Relevance
“…3,4) The most frequent RAA has no retroesophageal segment or mirror image branching (77%). RAA with a retroesophageal segment is rare (4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4) The most frequent RAA has no retroesophageal segment or mirror image branching (77%). RAA with a retroesophageal segment is rare (4%).…”
Section: Discussionmentioning
confidence: 99%
“…2) Our basic strategy for treatment of an aneurysm or dissection of the arch is total arch replacement. 3) However, to deal with the risks or problems associated with patients with RAA, we chose hybrid repair including the use of TEVAR for the three cases.…”
Section: Discussionmentioning
confidence: 99%
“…Ogino and colleagues have reported that they routinely use the graft-inversion technique called 'stepwise technique' for open distal aortic anastomosis under circulatory arrest [3]. They have reported that this technique is easy and useful to achieve favourable haemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques for performing this procedure have previously been documented. [4][5][6] Performing a precise distal anastomosis is critical in total arch replacement surgery because of the difficulty in controlling the bleeding from this site and the risk of a potentially fatal infection if there is an injury to the nearby esophagus or lung. While the malleable ring is still useful in some cases, we were challenged to develop an alternative because it was difficult to insert and make adjustments in the size.…”
Section: Techniquementioning
confidence: 99%